First International Consensus Report on Adnexal Masses: Management Recommendations. (7th March 2017) - Glanc, Phyllis; Benacerraf, Beryl; Bourne, Tom; Brown, Douglas; Coleman, Beverly G.; Crum, Christopher; Dodge, Jason; Levine, Deborah; Pavlik, Edward; Timmerman, Dirk; Ueland, Frederick R.; Wolfman, Wendy; et al.
Abstract : The First International Consensus Conference on Adnexal Masses was convened to thoroughly examine the state of the science and to formulate recommendations for clinical assessment and management. The panel included representatives of societies in the fields of gynecology, gynecologic oncology, radiology, and pathology and clinicians from Europe, Canada, and the United States. In the United States, there are approximately 9.1 surgeries per malignancy compared to the European International Ovarian Tumor Analysis center trials, with only 2.3 (oncology centers) and 5.9 (other centers) reported surgeries per malignancy, suggesting that there is room to improve our preoperative assessments. The American College of Obstetricians and Gynecologists Practice Bulletin on "Management of Adnexal Masses, " reaffirmed in 2015 ( Obstet Gynecol 2007; 110:201–214), still states, "With the exception of simple cysts on a transvaginal ultrasound finding, most pelvic masses in postmenopausal women will require surgical intervention." The panel concluded that patients would benefit not only from a more conservative approach to many benign adnexal masses but also from optimization of physician referral patterns to a gynecologic oncologist in cases of suspected ovarian malignancies. A number of next‐step options were offered to aid in management of cases with sonographically indeterminate adnexal masses. This process would provide an opportunity to improve risk stratification for indeterminate masses via the provision of alternatives, including but not limited to evidence‐based risk‐assessment algorithms and referral to an "expert sonologist" or to a gynecologic oncologist. The panel believed that these efforts to improve clinical management and preoperative triage patterns would ultimately improve patient care.